THE ROLE OF EXPERIMENT IN PRIMARY SCIENCE EDUCATION - GERHÁTOVÁ, Žaneta (Trends in education, 2011)
Integral part of science education is experiment. The paper presents the submission of project "Temperature measurement" via project learning with using integrated e-learning for science in 3th Class of primary school. The goal of integrated e-learning is to improve teaching of technical subjects and natural sciences via observations and active experiments of all kinds (real, real remote and virtual) as well as using the latest information and communication technologies.
Keywords: experiment; integrated e-learning; science education.